Electron-impact ionization of B3+ ions - Renwick, A.; Bray, Igor; Fursa, Dmitry; Jacobi, J.; Knopp, H.; Schippers, S. (Institute of Physics Publishing Ltd., 2009)
The electron-impact total ionization cross sections for B3+ have been determined both experimentally and theoretically. The experiment was carried out using a parent beam with B3+ ions in a mix of ground 11S and metastable 23S states. The convergent close-coupling (CCC) method has been used to calculate the corresponding cross sections and, by matching with experiment, the ratio of the initial target states in the beam has been determined. Good agreement with experiment across a broad energy range is obtained, particularly when indirect ionization processes are included in the calculations.